Secure traffic data propagation in Vehicular Ad Hoc Networks. (6th July 2010) - Aslam, Baber; Park, Soyoung; Zou, Cliff C.; Turgut, Damla
In vehicular ad hoc network, vehicles can share traffic/emergency information. The information should not be modified/manipulated during transmission without detection. We present two novel approaches to provide reliable traffic information propagation: two-directional data verification, and time-based data verification. The traffic message is sent through two (spatially or temporally spaced) channels. A recipient vehicle verifies the message integrity by checking if data received from both channels are matched. Compared with the popular public-key based security systems, the proposed approaches are much simpler and cheaper to implement, especially during the initial transition stage when a mature VANET network infrastructure does not exist.